Competencies of effective village leadership in Malaysia - Ahmad, Ani; Silong, Abu Daud; Abbasiyannejad, Mina (Muhammadon Centre for Research and Development, 2015)
In Malaysia, Village Development and Security Committee (VDSC) or locally known as Jawatankuasa Kemajuan dan Keselamatan Kampung (JKKK) is a community based-organization established by the Federal Government to perform village administration and development. This organization is considered as the village leadership. It consists of at least ten to fifteen members with the village head as chairman and holds an important place in the political, economic, sociocultural systems in this country. A survey of literatures on village leadership shows that only very few studies have been done on the issue of village leadership. Many works on this topic revolved round the role of village leaders, and mainly found in China, Thailand and India. This paper is an effort to contribute to the subject of village leadership in the Malaysian context. This study aims to explore the competencies of effective village leaders in award winning villages in Malaysia. Thrusting upon the qualitative paradigm, the leadership competencies of nine effective village leaders have been explored through semi-structured interviews. The atlasti software version 7.1.5 was used to analyze data and to generated themes such as skills in acquiring funds and resources for village development, writing and presentation skills, entrepreneurship skills, creativity skills in delegating task, and interpersonal skills. These skills are required competencies for village leaders. Findings from this paper can be utilized to improve leadership skills of other village leaders in Malaysia. The findings also implies that some unique attributes in the characteristics of these leaders are common, and can be further explored as a base for the development of capacity building for similar categories of leaders in other villages.